Pengembangan Ensiklopedia Berbasis Potensi Lokal Yang Terdapat Di Wakatobi Pada Materi Pokok Animalia Invertebrata (Mollusca Dan Echinodermata) - rosnawati, veni; kaharudin, la ode (Universitas Negeri Makassar, 2020)
Encyclopedia Development Based on Local Potential in Wakatobi on Animalia Invertebrates (Mollusca and Echinodermata) material. The study aims at producing Encyclopedia based on local potential as learning source which has specifications and valid, practical as well and effective. The study was a research and development (Research & Development / R & D), adapted the ADDIE model which consisted of 5 stages, namely: (1) Analysis; (2) Design; (3) Development (4) Implementation; and (5) Evaluation. Data collection used validation questionnaire to exame validation of the encyclopedia based on local potential, questionnaire of teacher and student’ responses to exime the practicality of encyclopedia based on local potential, and learning result test to exime the effectiveness of encyclopedia based on local potential. Data were obtained from the result of analysis using descriptive statistics analysis. The results shows that specifications encyclopedia based on local potential which had been developed presented the material with the local animal pictures. The results of the study reveal that the total mean score of encyclopedia validity based on local potential overall is in valid category (4,23), the overall teacher’s response is in positive category (89,23), and student’ response is in very psitive category (82.83%), and it has met the practical criteria. The encyclopedia based on local potential has also met the effective criteria that 35 students passed according to the criteria, which is over 80% passed medium criteria.